THE ROLE OF GRAMMATICAL CATEGORIES IN SHAPING COGNITION AND CULTURE: A COGNITIVE LINGUISTIC PERSPECTIVE - O’rozboyeva Mavluda Shukurlo qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This approach explains the connection between language structure and cognitive processes, suggesting that categories such as "time," "activity," and "place" reflect how individuals perceive and organize reality. Grammatical categories, including tense and aspect, convey not only time-related information but also nuances about the nature of actions, their duration, and completion. The present study explores the impact of grammatical categories on thought processes and highlights the role of language in reflecting culture, worldview, and social dynamics. Additionally, cognitive linguistics offers insight into how different languages categorize time and events, exemplified by variations in tense structures across languages like Russian. Keywords: Cognitive linguistics, grammatical categories, tense, aspect, language and cognition, worldview, language structure, time categories, semantics, syntax, cultural differences.